Acute in vitro hypoxia and high-altitude (4,559 m) exposure decreases leukocyte oxygen consumption - Faoro, Vitalie; Fink, Bruno; Taudorf, Sarah; Dehnert, Christoph; Berger, Marc M.; Swenson, Erik R.; Bailey, Damian M.; Bärtsch, Peter; Mairbäurl, Heimo (American journal of physiology. Regulatory, integrative and comparative physiology, 2011)
Hypoxia impairs metabolic functions by decreasing activity and expression of ATP-consuming processes. To separate hypoxia from systemic effects, we tested whether hypoxia at high altitude affects basal and PMA-stimulated leukocyte metabolism and how this compares to acute (15 min) and 24 h of in vitro hypoxia. Leukocytes were prepared at low altitude and ∼24 h after arrival at 4559 m. Mitochondrial oxygen consumption (JO2) was measured by respirometry, oxygen radicals by electron spin resonance spectroscopy, both at a Po2 = 100 mmHg (JO2,100) and 20 mmHg (JO2,20). Acute hypoxia of leukocytes decreased JO2 at low altitude. Exposure to high altitude decreased JO2,100, whereas JO2,20 was not affected. Acute hypoxia of low-altitude samples decreased the activity of complexes I, II, and III. At high altitude, activity of complexes I and III were decreased when measured in normoxia. Stimulation of leukocytes with PMA increased JO2,100 at low (twofold) and high altitude (five-fold). At both locations, PMA-stimulated JO2 was decreased by acute hypoxia. Basal and PMA-stimulated reactive oxygen species (ROS) production were unchanged at high altitude. Separate in vitro experiments performed at low altitude show that ∼75% of PMA-induced increase in JO2 was due to increased extra-mitochondrial JO2 (JO2,res; in the presence of rotenone and antimycin A). JO2,res was doubled by PMA. Acute hypoxia decreased basal JO2,res by ∼70% and PMA-stimulated JO2,res by about 50% in cells cultured in normoxia and hypoxia (1.5% O2; 24 h). Conversely, 24 h in vitro hypoxia decreased mitochondrial JO2,100 and JO2,20, extra-mitochondrial, basal, and PMA-stimulated JO2 were not affected. These results show that 24 h of high altitude but not 24 h in vitro hypoxia decreased basal leukocyte metabolism, whereas PMA-induced JO2 and ROS formation were not affected, indicating that prolonged high-altitude hypoxia impairs mitochondrial metabolism but does not impair respiratory burst. In contrast, acute hypoxia impairs respiratory burst at either altitude.